Atom Probe Tomography: Development and Application to the Geosciences - Reddy, Steven; Saxey, David; Rickard, William; Fougerouse, Denis; Montalvo, S.D.; Verberne, R.; Van Riessen, Arie (WILEY, 2020)
Atom probe tomography (APT) is an analytical technique that provides quantitative three-dimensional elemental and isotopic analyses at sub-nanometre resolution across the whole periodic table. Although developed and mostly used in the materials science and semiconductor fields, recent years have seen increasing development and application in the geoscience and planetary science disciplines. Atom probe studies demonstrate compositional complexity at the nanoscale and provide fundamental new insights into the atom-scale mechanisms taking place in minerals over geological time. Here, we provide an overview of APT, including the historical development and technical aspects of the instrumentation, and the fundamentals of data acquisition, data processing and data reconstruction. We also review previous studies and highlight the potential future applications of nanoscale geochemical studies of natural materials.